Relationships between the Transition of a Kind of Coral in Inner Bay and Light Photon on a Seabed - AKI, Hiroshi; SHIMIZU, Rika; NAKANO, Susumu (PROCEEDINGS OF COASTAL ENGINEERING, JSCE, 2008)
The transition of a kind of coral from Acropora tumida to Lithophyllon undulatum was generated in the Takegashima Marine Park which is located in the border of Tokushima Pref. and Kochi Pref. The field observation of light photon on a seabed was conducted in 2006 and 2007 to clarify the cause of the transition. We investigated the method to estimate light photon on a seabed by using sunshiny data of the meteorological observing station on the basis of the results obtained from the observed photon data. We presumed the annual average value of light photon on a seabed and compared it with the habitat distribution of coral. It was clarified that a lot of Acropora tumida were living in the area where the amount of light photon was large.